Proper absolute extensor - Valov, Vesko (Topology Proceedings, 2023)
We describe the proper absolute (neighborhood) extensors for the class of at most $n$-dimensional spaces, notation $A(N) E_{p}(n)$. For example, the unique locally compact $n$-dimensional separable metric space $X \in AE_{p}(n)$ satisfiyng the $DD^{n}$ P-property is the space obtained by deleting a point from the $n$-dimensional Menger compactum. Non-metrizable $A(N) E_{p}(n)$-spaces are also described.